Pengaruh Social Media Marketing Terhadap Purchase Intention Di Teko Healthy Resto Medan - Jackie; Rina Friska B. Siahaan; Dewi Anggraini; Willi Chandra; Fauzi A.M. Hutabarat (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
Teko Healthy Resto is a restaurant that provides menus and food dishes with 100% natural ingredients from plants (Vegan).The purpose of this study is: "To find out and analyze the influence of Social Media Marketing on Purchase Intention at Teko Healthy Resto, Medan". According to Gunelius (2011) there are four indicators of social media marketing, namely: Content Creation, Content Sharing, Connecting, Community Building. This study uses associative quantitative research methods. The sample of this study were customers at Teko Healthy Resto, Medan. Sampling using incidental sampling / accidental sampling is a sampling technique based on chance, that is, any patient who coincidentally meets the researcher can be used as a sample.the correlation value is 0.596 in the range 0.40 – 0.599 (enough) which means that Social Media Marketing and Purchase Intention have a positive correlation. And for the results of simple linear regression, namely; Y = 7.521 + 0.769X which means that the Constant is 7.521; it means that if Social Media Marketing value is 0, then Purchase Intention value is 7.521, The value Coefficient of Determination is 0.355, which means that the influence of the Social Media Marketing (X) variable on the Purchase Intention (Y) variable is 35.5%.